Effects of different nitrogen doses on thymoquinone and fatty acid composition in seed oil of black cumin (Nigella sativa L.). (26th December 2021) - Telci, Isa; Izgi, Mehmet Necat; Ozek, Temel; Yasak, Selma; Yur, Suleyman; Ozek, Gulmira
Abstract: Black cumin, Nigella sativa L. belonging to Ranunculaceae, is a valuable medicinal plant because of the curative effects of seed and oil. Despite studies on black cumin, there are few studies on the effects of nitrogen on fatty acid composition, no records on thymoquinone yield, and the thymoquinone content of the seed oil. In this study, the effects of different nitrogen doses on the seed oil yield, thymoquinone ratio/yield, and fatty acid compositions were investigated. Field studies with nitrogen doses (0, 40, 60, 80, and 100 kg/ha) were studied using the randomized plot design. As a result of the research, nitrogen doses significantly affected the oil and thymoquinone yields while insignificant on the thymoquinone ratio. The highest oil yield with 501.6 kg/ha was obtained from 80 kg/ha of the nitrogen doses, while the highest thymoquinone yield with 10.24 kg/ha was obtained from the control plots. Thymoquinone yields were in the same statistical group with other nitrogen doses, except for means of 100 kg/ha nitrogen doses. Linoleic, oleic, and palmitic acids were major fatty acids of black cumin, and their variations were insignificant in nitrogen applications. The values of butyric, capric, and linolenic acids varied significantly in different nitrogen doses. As a result of the study, it was determined that the highest oil yield was obtained from 80 kg/ha nitrogen application. It has been determined that nitrogen doses above 60–80 kg/ha should be avoided for the seed oil and thymoquinone yields in black cumin.